Penghindaran Pajak : Suatu Kebijakan Atau Suatu Strategi Pada Perusahaan - Yuniastuti, Rina Milyati; Nasyaroeka, Jhon (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
This research focuses on whether a tax avoidance policy or a strategy is carried out in manufacturing companies. The policy variable uses managerial ownership with the Good Corporate Governance factor and for strategy uses business risk/company risk variables. The research was conducted using data from three years 2019-2021 with 84 manufacturing companies. The research method uses quantitative statistical analysis methods. And the sample was taken using purposive sampling method. The results of the study stated that managerial ownership has the most dominant effect compared to business risk/company risk on tax evasion. Company policies with Good Corporate Governance factors are more accurate dominant than the company's business risk strategy for not doing tax evasion.Keywords: Tax Avoidance, Managerial Ownership, Good Corporate Governance, Business risk